2002
DOI: 10.1016/s0092-8674(02)01085-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Destabilization of HIF-1α by ARD1-Mediated Acetylation

Abstract: Hypoxia-inducible factor 1 (HIF-1) plays a central role in cellular adaptation to changes in oxygen availability. Recently, prolyl hydroxylation was identified as a key regulatory event that targets the HIF-1alpha subunit for proteasomal degradation via the pVHL ubiquitination complex. In this report, we reveal an important function for ARD1 in mammalian cells as a protein acetyltransferase by direct binding to HIF-1alpha to regulate its stability. We present further evidence showing that ARD1-mediated acetyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
563
3
18

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(604 citation statements)
references
References 48 publications
20
563
3
18
Order By: Relevance
“…In the presence of oxygen, prolyl hydroxylases (known as prolylhydroxylase-domain protein 1-3), modify Hif-1a and thereby allow it to interact with the von Hippel Lindau (VHL) complex resulting in ubiquitination and proteasomal degradation of Hif-1a (Semenza, 2001). Moreover, O 2 -dependent hydroxylation of Hif-1a by the enzyme factor inhibiting Hif-1 blocks the interaction of Hif-1a with the transcriptional coactivator p300/CBP and therefore inhibits HIF-1 mediated gene transcription under normoxic conditions (Jeong et al, 2002). During hypoxia the rate of asparagine and proline hydroxylation decreases, VHL cannot bind anymore to Hif-1a, and thus the protein remains stable.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of oxygen, prolyl hydroxylases (known as prolylhydroxylase-domain protein 1-3), modify Hif-1a and thereby allow it to interact with the von Hippel Lindau (VHL) complex resulting in ubiquitination and proteasomal degradation of Hif-1a (Semenza, 2001). Moreover, O 2 -dependent hydroxylation of Hif-1a by the enzyme factor inhibiting Hif-1 blocks the interaction of Hif-1a with the transcriptional coactivator p300/CBP and therefore inhibits HIF-1 mediated gene transcription under normoxic conditions (Jeong et al, 2002). During hypoxia the rate of asparagine and proline hydroxylation decreases, VHL cannot bind anymore to Hif-1a, and thus the protein remains stable.…”
Section: Introductionmentioning
confidence: 99%
“…GST, glutathione-S-transferase; HBx, HBV regulatory protein; HIF-1a, hypoxia-inducible factor-1a; ODD, oxygen-dependent degradation; WT, wild type. Jeong et al, 2002;Qian et al, 2006), the acetylation hypothesis remains controversial since human ARD1 does not, at least directly, acetylate HIF1a (Arnesen et al, 2005;Bilton et al, 2005Bilton et al, , 2006Fisher et al, 2005;Murray-Rust et al, 2006). Instead, diverse other mechanisms have been proposed for the HDAC inhibitor-induced HIF-1 regulation; Kong et al (2006) showed that HDAC inhibitors induced the proteasomal degradation of HIF-1a by interacting with HSP70 and thereby disrupted the HSP70/HSP90 axis function.…”
Section: Discussionmentioning
confidence: 99%
“…Specific prolyl hydroxylases (PHDs) catalyse the hydroxylation of these proline residues in an oxygen-dependent manner (Brahimi-Horn et al, 2005). Recent investigations suggest that acetyltransferases and histone deacetylases (HDACs) may have a role in the regulation of stability and transcriptional activity of HIF-1a (Jeong et al, 2002;Chang et al, 2006;Yoo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…HDACi can induce HIF-1a degradation by acetylation at Lys532, leading to the interaction with, and ubiquitination by pVHL (Jeong et al, 2002). Further, HDACi can induce HIF-1a degradation in a VHL-independent mechanism .…”
Section: Hdaci Inhibits Angiogenesismentioning
confidence: 99%